A Geospatial Approach to Mapping Municipal Solid Waste Disposal Patterns: A Case Study of Uyo Metropolis, Nigeria - Ettang, I. D.; Eyoefen, I. E. (Journal of Spatial Information Sciences, 2026)
Rapid urbanization in Nigerian cities like Uyo Metropolis has exacerbated municipal solid waste (MSW) management challenges, leading to widespread illegal dumping, environmental degradation, and public health risks. This study attempts to simulate waste disposal patterns in Uyo Metropolis of Akwa Ibom State, Nigeria, using geospatial. Sentinel-2 satellite image of 2026 was acquired and processed in Google Earth Engine (GEE) to compute spectral indices. Spatial analyses included distribution mapping, multi-ring buffering (300 m, 500 m, 800 m), Hotspot analysis (1,000 m threshold), and kernel density estimation (1,500 m radius), with overlays on reclassified indices. Results revealed a non-random, road-centric distribution, with dumpsites clustering along key arteries like Ikot Ekpene, Oron, Nwaniba, and Abak Roads, forming linear and nodal patterns in the urban core. The trend reveals solid waste disposal occurring in highly populated areas with heavy concentration of human activities. High-confidence hotspots (95–99%) were concentrated centrally, aligning with high/very high Urban Index classes and high/very high NDBaI bareness zones. These indicate that accessibility, impervious surfaces, and land exposure as key drivers of indiscriminate dumping system. The application of geospatial framework offers a cost-effective tool for prioritizing interventions to mitigate illegal dumping and promote resilient urban planning.